Julius Zeyer i Stanisław Wyspiański. Modernistyczny projekt krytycznej mitologii narodowej - Mielczarek, Joanna (Collectanea Philologica, 2014)
The Czech and Polish modernistic project of the critical national mythology is, in general, a form of the artist’s discussion with his own cultural tradition which was represented by the common, collective awareness. This collective awareness was, at that time, deprived of official form, due to the lack of state independence. In the works of Stanisław Wyspiański and Julius Zeyer, we can see the aspiration to achieve the recent, non-fixed look at the national tradition in its literary shape. There was the idea of tragic conflict which has been used by Wyspiański, first of all, in the cycle of his historical plays: Bolesław Śmiały and Skałka. Julius Zeyer’s most famous work, the epic poem named Vyšehrad, refers to the most important tradition of Czech romanticism, namely, to the way of the functioning of folklore in literary tradition. Zeyer also took up the discussion with the tradition of the alleged medieval manuscripts (the so-called Rukopis královédvorský and Rukopis zelenohorský) and suggested a critical using of national mythology. Critical – in this case – means: non-particular, non-provincial, opened to influence and reinterpretation.